Clinical researchThe estimation of clinical and home-based tilt training efficacy - Kozłowski, Dariusz; Łepska, Lidia; Zapaśnik, Patrycja; Budrejko, Szymon; Kozłowska, Magdalena; Sidłowska, Edyta; Lewicka-Nowak, Ewa; Dąbrowska-Kugacka, Alicja; Dudziak, Maria; Raczak, Grzegorz (Archives of Medical Science, 2007)
Introduction: Tilt training is a method of treatment of vasovagal patients. Two strategies make it possible to be performed as clinical and home-based training. The aim of the study was an attempt to compare the efficacy of the two types of training. Material and methods: The investigation was carried out on a group of 49 patients, between the ages of 16 and 73 (average 37.4±17.0) with recurrent syncopal episodes and positive head-up tilt test. To obtain a positive vasovagal reaction we used 4 different protocols: passive without any provocation test (pass-test), active using nitroglycerin (ntg-test), adenosine (adn-test), physiological fluid infusion (fluid-test). The patients were randomized into two groups – those treated in clinical and home-based tilt training. In both groups the criterion of efficacy was gaining the effect of 45 minutes of uninterrupted standing. The remote effect was also assessed – a relapse of syncope during 6 months of observation. Results: In the group of patients treated in clinical conditions, the efficacy of training was 69%, compared with 56% among patients treated by home-based tilt training. A relapse of syncope occurred in both groups with comparable frequency (41 vs. 36%) during 6 months of observation. Conclusions: Both variants of tilt training are characterized by a similar long-term efficacy. The type of method applied should be mainly dependent on the abilities and preferences of the patient.